Bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II) anchored onto chloromethylated polystyrene for the biomimetic oxidative coupling of 2-aminophenol to 2-aminophenoxazine-3-one - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
2-(alpha-Hydroxyethyl)benzimidazole (Hhebmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This polymer-anchored chelating resin reacts with cupric acetate in presence of Hhebmz to give polymer-anchored copper(II) complex PS-[Cu(hebmz)(2)]. Elemental analyses, FT-IR, electronic, scanning electron micrographs (SEM) and TGA-DTA pattern have been used to characterize the complex. Oxidative coupling of 2-aminophenol (OAP) to 2-aminophenoxazine-3-one (APX) catalyzed by PS-[Cu(hebmz)(2)] in presence of air at 70 degrees C in DMF gave 62% substrate conversion over a period of 8 h. Kinetics of the above reaction indicated that the rate of oxidative coupling of OAP has a first order dependence with respect to substrate, catalyst and air pressure (dissolved O-2) concentrations in the range of conditions evaluated. Based on these observations, a plausible mechanism for the above reaction has been proposed. From, the study on the effect of temperature on the rates of oxidative coupling, an activation energy 34.2 kcal/degree mole was evaluated from Arrhenius plot of -ln rate versus 1/T. Enthalpy, entropy and free energy were calculated using standard thermodynamic equations for the above reaction. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-aminophenol; 2-aminophenoxazine-3-one; bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II); chloromethylated polystyrene; oxidative coupling

Synthesis, characterization and catalytic potentials of polymer anchored copper(II), oxovanadium(IV) and dioxomolybdenum(VI) complexes of 2-(alpha-hydroxymethyl)benzimidazole - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Manikandan, Palanichamy; Halligudi, Shivappa B. (Reactive & Functional Polymers, 2005)
{2-(alpha-Hydroxymethyl)benzimidazole (Hhmbmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This chelating resin reacts with cupric acetate, vanadyl sulphate and [MoO(2)-(acac)(2)] (Hacac = acetylacetone) in presence of Hhmbmz to give complexes PS-[Cu(hmbmz)(2)], PS-[VO(hmbmz)(2)] and PS-[MoO(2)(hmbmz)(2)] (where
Keywords: 2-(alpha-hydroxymethyl)benzimidazole; oxidation of styrene and ethyl benzene; oxidative bromination of salicylaldehyde; polymer anchored-complexes